What happens in an estuary doesn't stay there: patterns of biotic connectivity resulting from long term ecological research - Mather, Martha E .; Finn, John T.; Kennedy, Cristina G.; Deegan, Linda A.; Smith, Joseph M. (My University, 2013)
The paucity of data on migratory connections and an incomplete understanding of how mobile organisms use geographically separate areas have been obstacles to understanding coastal dynamics. Research on acoustically tagged striped bass (Morone saxatilis) at the Plum Island Ecosystems (PIE) Long Term Ecological Research site, Massachusetts, documents intriguing patterns of biotic connectivity (i.e., long-distance migration between geographically distinct areas). First, the striped bass tagged at PIE migrated southward along the coast using different routes. Second, these tagged fish exhibited strong fidelity and specificity to PIE. For example, across multiple years, tagged striped bass resided in PIE waters for an average of 1.5–2.5 months per year (means: 51–72 days; range 2–122 days), left this estuary in fall, then returned in subsequent years. Third, this specificity and fidelity connected PIE to other locations. The fish exported nutrients and energy to at least three other coastal locations through biomass added as growth. These results demonstrate that what happens in an individual estuary can affect other estuaries. Striped bass that use tightly connected routes to feed in specific estuaries should have greater across-system impacts than fish that are equally likely to go anywhere. Consequently, variations in when, where, and how fish migrate can alter across-estuary impacts.
Keywords: Estuaries; Migratory connections; Striped bass; Plum Island Ecosystems Long Term Ecological Research site